Clinical evaluation of hirsutism in South India - Subha, R.; Tharini, G. K. (International Journal of Research in Dermatology, 2018)
Background: Hirsutism is defined as the presence of terminal coarse hairs in women, in male distribution. Hirsutism affects approximately 5 to 10% of women of reproductive age. There are only very few studies from south India on associations of hirsutism. We analyzed the prevalence of hirsutism among different age groups, etiology and its associated conditions. Methods: This prospective study was conducted in the Department of Dermatology, of a tertiary hospital in south India over a period of two years. Patients with Ferriman Gallway score of 8 or more were included in the study. Complete history, examination and investigations including USG abdomen & pelvis, hormonal assay were done for all patients. All our patients were screened for metabolic syndrome. Results: A total of 73 patients with hirsutism were enrolled. Among them, 53 (72.6%) were in the age group of 15 to 35 years. Menstrual irregularities were seen in 35 patients (48%). Face was the commonest site of involvement. Serum total testosterone was elevated in 10 patients (13.7%). LH, FSH ratio was more than 2 in 12 patients (16.4%). Polycystic ovaries were seen on pelvic ultrasonogram in 20 patients (27.3%). Conclusions: Idiopathic hirsutism was the most common cause of hirsutism in our study. In our study 30% of patients were obese. Among them, features of metabolic syndrome were seen in 31.8%, though majority of our patients were young.